Inner Engineering: A Yogi's Guide to Joy - Sadhguru (Penguin Random House, 2016)
Inner Engineering is a fascinating read, rich with Sadhguru s insights and his teachings. If you are ready, it is a tool to help awaken your own inner intelligence, the ultimate and supreme genius that mirrors the wisdom of the cosmos Deepak Chopra In his revolutionary new book, visionary, mystic and yogi Sadhguru distils his own experiences with spirituality and yoga and introduces the transformational concept of Inner Engineering. Developed by him over several years, this powerful practice serves to align the mind and the body with energies around and within, creating a world of limitless power and possibilities. Inner Engineering is your own software for joy and well-being